The results of studies on ribonuclease from king cobra venom (Ophiophagus hannah) - Thiet, Nguyen Van (Academia Journal of Biology, 2014)
In this paper Ribonuclease (RNase) from Vietnam king cobra (Ophiophagus hannah) venom was characterized in detail by ion-exchange chromatographic methods and its some properties were studied. It seems that king cobra venom RNase is very thermostable: treatment by heating enzyme solutions (in a water bath) for 5 min at temperature from 70oC to 100oC almost does not abolish its activity. The existence of this enzyme in multiple molecular forms was confirmed by chromatographic methods, including ion-exchange chromatography on columns with CM-cellulose and SP Sepharose 4 Fast Flow and gel-filtration on columns with Superdex 200 and Superdex 75. These methods have revealed at least 4 molecular forms of this enzyme differing in net charge and 4 forms differing in molecular size. The enzyme is the most active in the pH range of 1.5 - 4.0 and its pH optimum is about 2.00 ± 0.25 in glycine or in mix glycine-citrate (in a ratio 1: 1) buffers. These properties of RNase from Vietnam king cobra venom is very similar to those ones of the enzyme from Vietnam cobra venom.